Emotion Analysis of Cross-Media Writing Text in the Context of Big Data - Ren, Rui (Frontiers in Psychology, 2022)
Since the beginning of the 21st century, sentiment analysis has been one of the most active research fields in natural language processing. Now sentiment analysis technology has not only achieved significant results in academia but also has been widely used in practice. From business services to political campaigns, sentiment analysis is used in more and more fields. Sentiment analysis is essentially to dig out the user's emotional attitude from the massive emotional natural language text data, and analyze the emotional dynamics of the text author through certain technical means. At present, there is almost no sentiment analysis in cross-media writing content, and it can rarely help cross-media writing vision to advance with the times and comprehensive improvement of writing ability to adapt to the current rapidly developing information society; the commonly used text media in the digital age are not Then there is the only composition tool. Various new media appearing with the development of the ages continue to intervene in writing, and it is the general trend to cultivate media literacy in writing. The main content of this paper is the research on the emotional intensity of Internet public Aiming at the shortcomings of the topic feature word selection in the sentiment tendency analysis of the Internet public opinion, improvements have been made to facilitate the research on the sentiment intensity of the sentiment analysis of the Internet public opinion.